2020
DOI: 10.1101/2020.05.21.102335
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase-dependent closed-loop modulation of neural oscillations in vivo

Abstract: Normal brain function is associated with an assortment of oscillations of various frequencies, each reflecting the timing of separate computational processes and levels of synchronization within and between brain areas. Stimulation accurately delivered on a specified phase of a given oscillation provides the opportunity to target individual aspects of brain function. To achieve this, we have developed a highly responsive system to produce a continuous online phase-estimate. In addition to stable oscillations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…For other approaches, it could be possible to utilise the lower amplitude information. Several authors have postulated that phase-dependent stimulation could be an effective therapeutic strategy for treating motor symptoms ( Rosin et al, 2011 ; Azodi-Avval and Gharabaghi, 2015 ; Holt et al, 2016 ; Meidahl et al, 2017 ) and we have recently demonstrated the potential efficacy of this approach ( Holt et al, 2019 ; McNamara et al, 2020 ).…”
Section: Discussionmentioning
confidence: 71%
“…For other approaches, it could be possible to utilise the lower amplitude information. Several authors have postulated that phase-dependent stimulation could be an effective therapeutic strategy for treating motor symptoms ( Rosin et al, 2011 ; Azodi-Avval and Gharabaghi, 2015 ; Holt et al, 2016 ; Meidahl et al, 2017 ) and we have recently demonstrated the potential efficacy of this approach ( Holt et al, 2019 ; McNamara et al, 2020 ).…”
Section: Discussionmentioning
confidence: 71%
“…Additionally tracking phase may augment therapeutic benefit, though, by delivering stimulation pulses at specific points within the oscillatory cycle. This has been shown to effectively disrupt pathological oscillations [10][11][12]17 . So far, to our knowledge, adaptive stimulation algorithms integrating both the phase and amplitude of a signal have not been established yet.…”
Section: Discussionmentioning
confidence: 99%
“…A special application is developing efficient sensing algorithms for adaptive deep brain stimulation, a recent advancement of a widely used treatment option for Parkinson's disease and other neurological disorders 5 . One of the directions in this development is to adjust stimulation parameters according to a peripheral or neurophysiological signal's phase and amplitude computed on the fly [6][7][8][9][10][11][12] . The popular approach to phase and amplitude estimation is to exploit the analytic signal approach based on the Hilbert Transform (HT) or, equivalently, the wavelet transform with a complex wavelet 1,[13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, adaptive DBS for Parkinson's disease is being trialled in humans, but this is currently limited to adjusting the amplitude of open-loop stimulation (Arlotti et al, 2018). However, phase-dependent electrical stimulation delivered to the globus pallidus has recently been used to disrupt pathological oscillations recorded in the overlying cortex of rodents (McNamara et al, 2020), while optogenetics would allow such stimulation to be controlled in realtime by abnormal activity recorded from the local network without interference from artefacts. Optogenetic therapies for epilepsy have been demonstrated in rodent models, but thus far these consist of continuous inhibitory stimulation delivered once a seizure is detected (Paz et al, 2013, Krook-Magnuson et al, 2013.…”
Section: Discussionmentioning
confidence: 99%